TARGET DAN REALISASI PAJAK DAERAH DI KABUPATEN MINAHASA UTARA - Marini ., Loho; Charles R. Ngangi; Caroline B. D. Pakasi (AGRI-SOSIOEKONOMI, 2018)
The objective of the research is to analyze the target and realization of tax revenue in North Minahasa Regency. The study was conducted from September to November of 2017. The data used were secondary data. Data collection techniques used are to go directly to the local revenue department and conduct interviews and make the necessary data recording. Method of data processing using trend analysis method. The results of the research showed that the Local Tax has a great influence on development in North Minahasa Regency and Development in North Minahasa Regency. It is increasingly seen clearly, in the construction of housing, warehouses and tourist places. It can also be seen from tax return projection for the next five years that is alwasy growing every year.*jnkd*.